K.J. Lee's essential otolaryngology head & neck surgery - Chan, Yvonne, 1973-; Goddard, John C. (John Christopher) (McGraw-Hill Education, 2016)
The leading guide in otolaryngology - invaluable for board review or as a clinical refresher